Role of interleukin 1β and interleukin 10 variants on ocular toxoplasmosis in Brazilian individuals - Araujo, Warlen Miiller Rocha; Ayo, Christiane Maria; Previato, Mariana; de Faria, Geraldo Magela; Frederico, Fábio Batista; Siqueira, Rubens Camargo; de Almeida, Gildásio Castello; Pereira-Chioccola, Vera Lúcia; de Mattos, Luiz Carlos; Brandão, Cinara Cássia (Frontiers in Ophthalmology, 2023)
Ocular toxoplasmosis (OT) is an intraocular inflammation that affects the retina and choroid, giving rise to posterior uveitis caused by Toxoplasma gondii infection. Genetic polymorphisms in cytokine genes may exert influence in the expression of these molecules and play a significant role in inflammatory responses and susceptibility to OT. The aim of this study was to evaluate the role of polymorphisms rs16944 (−511 C>T) of the interleukin (IL) 1β gene and rs1800896 (-1082 G>A) of the IL10 gene on OT in Brazilian individuals with serological diagnosis of T. gondii and after conducting fundoscopic exams. Participants with positive serology were classified into two distinct groups according to the presence (G1; n=110) or absence (G2; n=104) of OT. The control group (G3) consisted of individuals without the infection (n=108). It was observed that the C/C genotype referring to the IL1β gene polymorphism was associated as a protective factor for OT (p=0.02, OR=0.28, CI 95 % 0.08 - 0.78 for G1 vs. G2 and p=0.03; OR=0.29, CI 95 %=0.09 - 0.82 for G1 vs. G3); while the heterozygous T/C genotype was associated as a risk factor for the occurrence of OT (p=0.05, OR=2.05, CI 95 %=1.03 – 4.16 for G1 vs. G2 and p=0.0004; OR=3.30, CI 95 %=1.72 – 6.52 for G1 vs. G3). In conclusion, the -511 C>T polymorphism of the IL1β gene seems to exert an important role for the pathogenesis of OT in Brazilian individuals.